2016
DOI: 10.1016/j.jaci.2015.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recruitment of CD14+ monocytes in experimentally induced allergic rhinitis in human subjects

Abstract: Our findings suggest that the mononuclear phagocyte population is directly involved in the production of proinflammatory chemokines that attract other immune cells. Rapid recruitment of CD14(+) monocytes to the challenged site indicates that these proinflammatory mononuclear phagocytes have a central role in orchestrating local allergic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 40 publications
10
64
4
1
Order By: Relevance
“…| 1633 respiratory mucosa. This observation was consistent with our previous study, 10 and further substantiated the finding that monocytes are recruited in large numbers to the challenged nasal mucosa of AR patients, whereas the density of macrophages remains unchanged. 17 Furthermore, we recently reported that blood monocytes constitutively migrate into the intestinal mucosa where they develop into mature macrophages, with a progressive loss of S100A8/A9 expression as part of the differentiation process.…”
Section: Flow Cytometric Analysis Of Blood Monocytessupporting
confidence: 93%
See 3 more Smart Citations
“…| 1633 respiratory mucosa. This observation was consistent with our previous study, 10 and further substantiated the finding that monocytes are recruited in large numbers to the challenged nasal mucosa of AR patients, whereas the density of macrophages remains unchanged. 17 Furthermore, we recently reported that blood monocytes constitutively migrate into the intestinal mucosa where they develop into mature macrophages, with a progressive loss of S100A8/A9 expression as part of the differentiation process.…”
Section: Flow Cytometric Analysis Of Blood Monocytessupporting
confidence: 93%
“…This model of in vivo experimentally induced human AR induces typical AR symptoms, and the recruitment of eosinophils, as demonstrated in previous studies from our group 10,15. This model of in vivo experimentally induced human AR induces typical AR symptoms, and the recruitment of eosinophils, as demonstrated in previous studies from our group 10,15.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…184,185). In humans, inflammatory myeloid cells have been reported in several settings including eczema, 186 psoriasis, 187,188 skin sensitization, 189 allergic rhinitis, 190 coeliac disease, 191 inflammatory bowel disease, 192,193 synovitis and peritonitis. 24,194 Kinetics, surface markers, gene expression and even direct labelling suggest that monocytederived cells dominate these populations.…”
Section: Phenotype and Distributionmentioning
confidence: 99%